Macromolecule/Polymer-Iodine Complexes: An Update - Moulay, Saad (Recent Innovations in Chemical Engineering, 2019)
The great chemical affinity of molecular iodine towards several macromolecules and innumerable polymers allows the formation of macromolecule/polymer-iodine complexes, usually commensurate with the desired uses and applications. In many instances, the formation of such complexes occurs through a charge-transfer mechanism. The strength of the ensued complex is more accentuated by the presence of heteroatoms (nitrogen, oxygen, sulfur) and the π-conjugation induced moieties within the chemical structure of the polymer. A wide range of polymers with high specific surface areas and large total pore volumes are excellent candidates for iodine adsorption, suggesting their use in the removal of radioactive iodine in nuclear power plants. The recent results of iodine uptake by polysaccharides such as starch, chitin, chitosan, alginate, and cellulose are but novelties. Complexing vinyl polymers such as poly(N-vinyl-2-pyrrolidone), poly(vinyl pyridine), poly(vinyl alcohol), poly(vinyl chloride), poly(acrylonitrile), and polyacrylics, with molecular iodine revealed special chemistry, giving rise to polyiodide ions (In -) as the actual complexing agents. Carbon allotropes (graphene, graphene oxide, carbon nanotubes, amorphous carbons) and polyhydrocarbons are prone to interact with molecular iodine. The treatment of a broad set of polymers and macromolecules with molecular iodine is but a doping process that ends up with useful materials of enhanced properties such conductivity (electrical, ionic, thermal); in some cases, the obtained materials were of engineering applications. Complexation and doping materials with iodine are also aimed at ensuring the antimicrobial activity, particularly, for those intended for medical uses. In several cases, the impact of the iodine doping of polymer is the alteration of its morphology, as is the case of the disruption of the graphitic morphology of the graphene or graphene oxide.
Keywords: doping